A criterion for environmental assessment using Birnbaum–Saunders attribute control charts. Issue 7 (3rd August 2015) - Leiva, Victor; Marchant, Carolina; Ruggeri, Fabrizio; Saulo, Helton
<x xml:space="preserve">Abstract</x> Assessing environmental risk is useful for preventing adverse effects on human health in highly polluted cities. We design a criterion for environmental monitoring based on an attribute control chart for the number of dangerous contaminant levels when the concentration to be monitored follows a Birnbaum–Saunders distribution. This distribution is being widely applied to environmental data. We provide a novel justification for its usage in environmental sciences. The control coefficient and the minimum inspection concentration for the designed criterion are determined to yield the specified in‐control average run length, whereas the out‐of‐control case is obtained according to a shift in the target mean. A simulation study is conducted to evaluate the proposed criterion, which reports its performance to provide earlier alerts of out‐of‐control processes. An application with real‐world environmental data is carried out to validate its coherence with what is reported by the health authority. Copyright © 2015 John Wiley & Sons, Ltd.